2007
DOI: 10.1152/ajplung.00403.2005
|View full text |Cite
|
Sign up to set email alerts
|

CFTR inhibition mimics the cystic fibrosis inflammatory profile

Abstract: Primary airway epithelial cells grown in air-liquid interface differentiate into cultures that resemble native epithelium morphologically, express ion transport similar to those in vivo, and secrete cytokines in response to stimuli. Comparisons of cultures derived from normal and cystic fibrosis (CF) individuals are difficult to interpret due to genetic differences besides CFTR. The recently discovered CFTR inhibitor, CFTRinh-172, was used to create a CF model with its own control to test if loss of CFTR-Cl− c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
162
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(179 citation statements)
references
References 31 publications
16
162
1
Order By: Relevance
“…IB3-1 cell lines were incubated for 24 h with EUK-134 (50 g/ml; Alexis Biochemicals), TG inhibitor R283 (250 M), KCC009 (250 M), or cystamine (400 M; Sigma-Aldrich) followed or not by rosiglitazone for 6 h (10 M; Alexis Biochemicals). A549 and 16HBE cell lines were incubated for 1 h with H 2 O 2 (33) (2 mM; Sigma-Aldrich) and for 24 h with rotenone (1 M; Sigma-Aldrich) or buthionine sulfoximine (10 M; Sigma-Aldrich) in the presence or absence of EUK-134 as well as with CFTR-inh172 (20,22) (20 M;Calbiochem). A549 and 16HBE cell lines were also cultured under hypoxic conditions in a humidified hypoxia chamber (Cop Laboratories) for 1 h at 1% O 2 (5% CO 2 balance N 2 ), and temperature was maintained at 37°C (34).…”
Section: Cell Lines and Culturesmentioning
confidence: 99%
“…IB3-1 cell lines were incubated for 24 h with EUK-134 (50 g/ml; Alexis Biochemicals), TG inhibitor R283 (250 M), KCC009 (250 M), or cystamine (400 M; Sigma-Aldrich) followed or not by rosiglitazone for 6 h (10 M; Alexis Biochemicals). A549 and 16HBE cell lines were incubated for 1 h with H 2 O 2 (33) (2 mM; Sigma-Aldrich) and for 24 h with rotenone (1 M; Sigma-Aldrich) or buthionine sulfoximine (10 M; Sigma-Aldrich) in the presence or absence of EUK-134 as well as with CFTR-inh172 (20,22) (20 M;Calbiochem). A549 and 16HBE cell lines were also cultured under hypoxic conditions in a humidified hypoxia chamber (Cop Laboratories) for 1 h at 1% O 2 (5% CO 2 balance N 2 ), and temperature was maintained at 37°C (34).…”
Section: Cell Lines and Culturesmentioning
confidence: 99%
“…CF is characterised by an intense pulmonary inflammation, and NFkB upregulation is among its key markers. It is a major inflammatory transcription factor [29] partly responsible for the high levels of interleukin-8, among other inflammatory mediators [30,31]. In addition to the latter, NF-kB might also lead to the transcription of vasoactive and proliferative mediators, such as ET-1 for instance.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we had shown that the de novo expression of IκBα protein could be obtained in CF human bronchial epithelial cells following treatment with the flavonoid genistein [25]. Perez and colleagues have also observed that cultured primary normal human bronchial epithelial cells have significantly increased basal secretion of proinflammatory cytokines, nuclear NF-κB translocation and stimulated secretion when these cells are first treated with a new class of specific inhibitor of CFTR chloride conductance, CFTR inh-172 [39]. These data support the hypothesis that lack of CFTR activity in airway epithelial cells is responsible for the onset of the inflammatory cascade in the CF lung.…”
Section: Why Is It Important To Identify Molecular Factor(s) Associatmentioning
confidence: 99%